1982
DOI: 10.1080/03015521.1982.10427877
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some soil and pasture components on the growth of hill country pastures 1. Winter and spring production

Abstract: Aspect and land slope have a major influence on winter and spring pasture growth. Possible physiographic, soil, and plant factors contributing directly to this influence were examined across a range of microsites in steep North Island hill country. As land slope increased, organic and inorganic nitrogen in the soil decreased. Similarly, organic carbon decreased and this was associated with a decline in soil water-holding capacity. Soil water potentials were high during winter and spring and showed little effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 17 publications
(15 reference statements)
2
27
0
Order By: Relevance
“…Ramachandrudu and Thangam (2007) ( McNaught, 1961). Ledgard, et al, (1982) in New Zealand, evaluated the effects of cow urine and equivalent nitrogen, potassium, and sulphur treatments on pasture yield, botanical composition, herbage chemical composition and N fixation by clovers during winter and spring. They noticed that urine caused a large increase in ryegrass yield, entirely due to its N content.…”
Section: Introductionmentioning
confidence: 99%
“…Ramachandrudu and Thangam (2007) ( McNaught, 1961). Ledgard, et al, (1982) in New Zealand, evaluated the effects of cow urine and equivalent nitrogen, potassium, and sulphur treatments on pasture yield, botanical composition, herbage chemical composition and N fixation by clovers during winter and spring. They noticed that urine caused a large increase in ryegrass yield, entirely due to its N content.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Olsen P values were generally higher than those recorded on slip scars in the Wairarapa (Lambert et aI. 1984) and on steep hill country at Whatawhata (Ledgard et al 1982(Ledgard et al , 1983 and Ballantrae (Luscombe 1980(Luscombe , 1981. Additional support for generally satisfactory fertility levels, at least on pre-I 942 and 1970 scars, was provided by the foliar nutrient analyses.…”
Section: Discussionmentioning
confidence: 99%
“…(I) Higher· soil fertility levels, particularly on accumulation zones which are derived mainly from superficial material removed during slip erosion which is often more fertile and organic. (2) Reduced slope angle (Ledgard et al 1982). (3) Improved soil moisture holding capacity (Jackson 1967).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many factors contribute to declining production on steeper landforms. For example, Ledgard et al (1982) suggested that variation in organic C and total N can cause large differences in production on hill country pastures, and this variation declined with increasing slope at Whatawhata Research Station. They also suggested that nutrient transfer from steep sites to camp sites by grazing animals can cause large differences in total N and subsequent pasture production.…”
Section: Uneroded Landformsmentioning
confidence: 99%